Improving Halal Food Product Literacy among Micro and Small Enterprise Actors in Semarang, Central Java - Safrina Oksidriyani; Putri Tiara Rosha; Refani Alycia Kusuma; Bintang Rizqi Kurniawan; Ela Sri Faniyanti; Bela Prasasti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This community service program aimed to improve halal food product literacy among eight food Micro and Small Enterprises (MSEs) in Semarang. Methodology: Conducted from July 10 to August 6, 2025, the program involved three stages: preparation, multimodal education (face-to-face and online), and pre-post-test evaluation. A 25-item questionnaire covering halal concepts, certification procedures, applicable regulations, and halal production SOPs was used to measure knowledge gains on a 0–100 scale. Results: The mean knowledge score increased from 49.0 to 77.4 (? = +28.4 points). The largest gains were associated with the content on BPJPH certification procedures and the self-declaration pathway. All the participants expressed interest in pursuing formal certification. Conclusions: Structured, practically oriented halal literacy education effectively improves MSEs’ certification readiness. A replicable three-stage model combining direct engagement, multimodal delivery, and practical materials is proposed for adoption by universities, the Badan Penyelenggara Jaminan Produk Halal (BPJPH), and relevant institutions. Limitations: The small sample size and the absence of a control group limit the generalizability of the findings. Contributions: This study provides a replicable educational model for stakeholders seeking to accelerate halal certification uptake among food MSEs, enriching halal literacy literature in public health nutrition and food science.